The Qur'anic Textual Purity and Authenticity: A Diachronic Analysis - Ushama, Thameem (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
The Qur'anic Textual Purity and Authenticity: A Diachronic Analysis